Peran dan Kewenangan Wali Hakim Kepala Kantor Urusan Agama (KUA) dalam Menyelesaikan Permasalahan Wali Nasab yang Berbeda Agama dalam Pernikahan: Studi Kasus KUA Ciracas - Sidiq, Muhamad; Na’imah, Farida Ulvi (Media Hukum Indonesia (MHI), 2025)
This research aims to analyze the role and authority of the wali hakim (judge guardian) at the Office of Religious Affairs (KUA) in resolving issues concerning wali nasab (lineage guardian) of different religions in marriage, with a case study at KUA Ciracas, East Jakarta. The research focuses on understanding the mechanism of transferring wali nasab to wali hakim based on Article 23 of the Compilation of Islamic Law (KHI) and the Islamic jurisprudence perspective on this phenomenon. The research method employed is a qualitative approach with data collection techniques including in-depth interviews, participatory observation, and document study. The results show that the transfer of wali nasab to wali hakim occurs when the wali nasab is unable to fulfill their duties, especially in cases of religious differences between the wali nasab and the prospective bride or groom. Factors causing this transfer include the absence of the wali nasab, rejection by the wali nasab due to religious differences, and complex socio-cultural conditions. From a fiqh perspective, the transfer is permitted to ensure the validity of the marriage and protect the rights of the prospective bride or groom. However, the legal status of this transfer becomes controversial when a wali ab'ad (distant guardian) still exists, requiring deep interpretation based on fiqh principles and Article 23 of the KHI.